Modulation of Oxidative Stress-Induced Senescence during Non-Alcoholic Fatty Liver Disease (2022)
ABSTRACT: Non-alcoholic fatty liver disease is characterized by disturbed lipid metabolism and increased oxidative stress. These conditions lead to the activation of different cellular response mechanisms, including senescence. Cellular senescence constitutes an important response to injury in the liver. Recent findings show that chronic oxidative stress can induce senescence, and this might be a driving mechanism for NAFLD progression, aggravating the disturbance of lipid metabolism, organelle dysfunction, pro-inflammatory response and hepatocellular damage. In this context, the modulation of cellular senescence can be beneficial to ameliorate oxidative stress-related damage during NAFLD progression. This review focuses on the role of oxidative stress and senescence in the mechanisms leading to NAFLD and discusses the possibilities to modulate senescence as a therapeutic strategy in the treatment of NAFLD. Keywords: ER stress; ROS; lipid metabolism; mitochondrial dysfunction; non-alcoholic liver disease; oxidative stress; stress-induced senescence.